Distribuição geográfica e fonte alimentar de triatomíneos e o papel do cão como possível fonte de infecção do trypanosoma cruzi - SIQUEIRA, Rosângela Rosângela Vieira (2016)
Chagas' disease is caused by the protozoan called Trypanosoma cruzi, transmitted to man and animals mainly by hematophagous hemiptera of the genera Triatoma, Panstrongylus and Rhodnius, popularly known by barbers. Considering that colonization of the home is a risk factor for the transmission of T. cruzi to humans and companion animals, domestic and wild, it is necessary to identify the vulnerable areas of transmission of the protozoan. The objective of the study was to know the triatomine species prevalent in the region and to investigate flagellate protozoa morphologically similar to T. cruzi in feces of the triatomines captured by the health agents of the municipalities under the jurisdiction of the Regional Health Superintendence of Alfenas (SRS / Alfenas). Of the 7874 hemiptera received, 7846 (96.64%) were identified as hematophages, 24 (0.39%) as predators and 4 (0.05%) as phytophagous. Among the hematophages identified, 7842 (99,94%) belong to Genus Panstrongylus and megistus species, 1 (0.01%) to P. diasi and 3 (0.03%) to Rhodnius neglectus. As for the evolutionary stage 4937 (62.92%) were nymphs and 2363 (30.11%) adults e 546 (6,95%) exemplares estavam secos e não foi feita a distinção do estádio evolutivo. It can be concluded that P. megistus is the predominant T. cruzi vector in the studied municipalities. In this way, the capture and vector identification process will be more effective in entomological surveillance because the results suggest that the development cycle of the parasite remains in the region.